Relationship between compliance to quality indicators, volume, and outcomes in pancreatic cancer resection in a community hospital setting - Brown, Megan M; Redfern, Roberta E; McPhee, Michael D (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Objective: To calculate and compare adherence to pancreatic cancer care quality indicators and related outcomes at three hospitals within our health system and determine their relatedness. Design: Retrospective review of cancer registry data and patient charts from January 1, 2000 – December 31, 2010. Setting: Three hospitals performing pancreatic resections within a single health system. Patients: All patients undergoing resection for the treatment of pancreatic cancer. Main Outcome Measures: Adherence to published quality indicators, patient survival, and surgical and institutional variables related to mortality. Results: Complication, morbidity and mortality, and overall survival rates were similar between facilities and were comparable to previously reported values of similar volume facilities. Overall adherence to quality indicators was approximately 73%; compliance to indicators in the “outcome” and “efficiency” domains was highest, but adherence was not associated with clinical outcomes. Patient mortality was lowest at the highest volume hospital in our health system; however, surgeon volume was not predictive of outcomes. Conclusion: Use of quality indicators is valuable in determining quality of care and identifying weaknesses, allowing for a targeted approach to improve quality of care and the associated processes. However, adherence to these quality indicators is not necessarily indicative of outcomes.